Humeral Shaft Fracture With Placement of an Intramedullary Nail Through an Unrecognized Sarcoma. (February 2021) - Cullen, Mark M.; Okwumabua, Ebubechi; Flamant, Etienne M.; Ferlauto, Harrison R.; Brigman, Brian E.; Eward, William C.
Abstract : Case: A 72-year-old man underwent intramedullary nailing of a humeral diaphysis fracture with passage through an unrecognized pathologic fracture. Four months later, a biopsy of a soft-tissue mass in the arm revealed pleomorphic undifferentiated sarcoma. Only after local recurrence and forequarter amputation was the story of a pathologic fracture through undifferentiated pleomorphic sarcomas of bone clear. The patient developed metastatic disease and died after 2 years postoperatively. Discussion: Orthopaedic surgeons should consider sarcoma when assessing patients with fractures of unknown etiology and an inappropriate mechanism because the placement of an intramedullary device through a sarcoma of bone has consequences.